Culturicon design model: a case of designer’s validation process - Mohd Zhafri Mohd Zukhi; Husniza Husni; Azham Hussain (Penerbit Universiti Kebangsaan Malaysia, 2023)
As more people own smartphones, using visual elements like emoticons, emojis, and stickers in mobile messaging applications has become popular. Smartphone users have grown accustomed to using these visual elements because of their positive effects on communication through applications. Even Oxford Dictionary named one of these visual elements the word of the year. However, due to cultural differences, these visual elements have limitations such as limited selection, misinterpretation, and misuse. To overcome the limitations, this study presented a Culturicon Design Model combining cultural dimensions and Human-Computer Interaction icon design principles. In doing so, the model must be validated before its efficacy can be established. This paper aims to outline the designer’s validation process. The designer developed Culturicon samples based on the model as part of the validation process. Then, they validated the model by responding to the validation form. The findings revealed that all designers agreed that the model is understandable and practical for designing Culturicon.